Sinister and Changing Political Model in Costa Rica. Three Plays by Contemporary Female Playwrights. - Soto, Rodrigo (2014)
In this text three recent Costa Rican plays of contemporary female writers with political content are analyzed. The plays are analyzed in the light of the notions of the sinister (Schelling, Freud) and what I have elsewhere called the “myth of Costa Rican exceptionalism”. The works considered are: La Loca, Ana Istarú monologue, Dicen las paredes, by Ailyn Morera, y Pentadrama, by Claudia Barrionuevo and Walter Fernández.